2009
DOI: 10.1159/000201791
|View full text |Cite
|
Sign up to set email alerts
|

Hyperreninemia Characterizing Women with Polycystic Ovary Syndrome Improves after Metformin Therapy

Abstract: Background: Polycystic ovary syndrome (PCOS) is characterized by chronic anovulation, hyperandrogenemia and insulin resistance. Hyperreninemia is observed in insulin resistance and hyperandrogenemic states. Aims: To investigate the levels of total plasma renin and their possible relationship with insulin resistance and hyperandrogenemia and to explore the effect of metformin on these parameters in PCOS women. Methods: 48 PCOS women who were age- and body mass index (BMI)-matched with 21 healthy women were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 101 publications
2
11
0
Order By: Relevance
“…Aldosterone impairs endothelial function through increased NADPH oxidase activity and mitochondrial generation of reactive oxygen species, which decrease bioavailability of nitric oxide (15,32). The RALES study showed that spironolactone (25 mg), added to conventional therapy for chronic heart failure, dramatically reduced mortality (30). Yet, spironolactone in the study did not have a clinically significant hemodynamic effect.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Aldosterone impairs endothelial function through increased NADPH oxidase activity and mitochondrial generation of reactive oxygen species, which decrease bioavailability of nitric oxide (15,32). The RALES study showed that spironolactone (25 mg), added to conventional therapy for chronic heart failure, dramatically reduced mortality (30). Yet, spironolactone in the study did not have a clinically significant hemodynamic effect.…”
Section: Discussionmentioning
confidence: 96%
“…activity of the cytochrome was reported only at very high doses or under in vitro experimental conditions, for example in bovine and human adrenal cortical mitochondria (28,29). Spironolactone-induced improvement of endothelial function could also be in part a consequence of aldosterone antagonism, as shown in studies investigating chronic heart failure (30). PCOS patients were reported to have significantly increased aldosterone levels in comparison with controls, although values were still within the normal range (13).…”
Section: Discussionmentioning
confidence: 99%
“…The RAS is activated in women with PCOS, and telmisartan, an angiotensin AT1 receptor antagonist, reduces their blood pressure 42, 43 . We found that angiotensinogen mRNA expression was increased 10 fold in HAF rats.…”
Section: Discussionmentioning
confidence: 99%
“…The ovarian RAS can induce hyperandrogenism and contribute to the manifestation of PCOS. It is also known that baseline levels of renin are elevated in women with PCOS and correlate with serum androgen levels (32,33). Prorenin production has been detected in the theca cells (34), while the cystic follicles in PCOS have demonstrated increased production of renin and angiotensin II from theca and granulosa cells, as occurs in normal atretic ovarian follicles (35).…”
Section: Discussionmentioning
confidence: 99%